Supercritical Water Ethanol Reforming for Hydrogen Production: (Effect of Different Support on Nickel Based Catalyst in Supercritical Water Condition) - NOURI*, SIROUS; AMRAN†, TUAN (Asian Journal of Chemistry, 2009)
The aim of this work is to study the behaviour of different supports of nickel based catalyst for hydrogen production by supercritical water reforming of ethanol in high pressure. Catalytic tests have been performed at laboratory scale under high pressure and supercritical water condition. Catalyst characterization was carried out to identify catalytic properties such as, surface area, temperature programmed desorption (TPD) and temperature programmed reduction (TPR). The analyses of liquid and gas were carried out in different G.C. In present condition, the support effects well the physical and chemical properties of catalyst. γ-Alumina and YSZ increase the acid sites. The composition of product and production of hydrogen varies with different support. ZrO2 and YSZ make easier the reduction of nickel oxide at temperature blow 500 ºC and increase the ethanol conversion and hydrogen production. The product composi-tion depends not only to temperature but also to the degree of nickel oxide reduction over support. In low temperature, nickel oxide favorite production of C2H4, C2H6 and heavier compounds. ZrO2 and specially YSZ are the best support to produce hydrogen with less carbon monoxide.